Pengaruh Perilaku Merokok Orang Tua Terhadap Kaum Remaja Di HKBP Bagansiapiapi - Siburian, Donny Paskah Martianus; Siahaan, Sanggam M. L. (Jurnal Christian Humaniora, 2022)
Abstract:Our bodies are the temples of holy spirit (1 Corinthians 6:19) keeping the bodies healthy can be taken as one of keeping the holiness of the temples of holy spirit. One of some healthy living behavior is by not consuming cigarette, we are recommended to avoid it’s smoke. In addition to health reasons, smoking is also not good economically. The increase in smoking behavior in Indonesia, especially among teenagers, cannot be separated from the factors that influence their smoking behavior, such as the environment such as friends and family. The family can meant spesifically parents as the closest individu in a members in terms socialization process among the teenagers. The smoking behavior of the parents surely affects the smoking behavior of children. Even the teenagers get a smoking ban by their parents, but the parents smoking behavior are presented oftenly in front of their children without any hesitation. This study aims to deeply observe smoking habits among teenagers, especially the factors that affect the smoking behavior. We found there is a conception in the society that considered smoking as adult male culture. This study concentrate towards teenage boys congregation in HKBP Bagansiapiapi aged 10-15 years in, Rokan Hilir Regency, Riau Province, Indonesia. This study explain how smoking behavior in the presence of children become potential stimulation that develop children's smoking behavior. The prohibition gave by parents to avoid smoke for children if it is not accompanied by concrete actions can develop as a mistaken impulse that triggers smoking behavior. This paper explain how these impulses are processed and formed in behavioral actions for teenagers using sociology behavioral perspective.Keywords: smoking behavior, parents, teenagers, impulse, health Abstrak:Tubuh kita adalah bait Allah (1 Korintus 6:19). Menjaga kesehatan tubuh adalah tanggung jawab setiap orang sebagai tindakan menjaga kekudusan tubuh dan salah satu bentuk prilaku hidup sehat dapat diupayakan dengan menghindari asap rokok. Selain alasan tersebut merokok juga tidak baik secara ekonomis. Meningkatnya perilaku merokok di Indonesia terkhusus di kalangan remaja tidak terlepas dari faktor-faktor yang memengaruhinya, seperti lingkungan pertemanan dan keluarga. Keluarga dalam hal ini orang tua sebagai salah satu anggota keluarga terdekat dalam proses sosialisi remaja tanpa disadari memengaruhi prilaku merokok anak. Remaja mendapatkan larangan merokok oleh orang tua, namun orang tua sering tetap meranampilkan prilaku merokoknya di hadapan anak secara terbuka. Penelitian ini bertujuan menyelidiki kebiasaan merokok di kalangan remaja gereja terkhusus pada pengaruh perilaku merokok orang tua yang dianggap sebagai budaya pria dewasa terhadap anak remaja laki-laki usia 10-15 tahun di Gereja HKBP Bagansiapiapi, Kabupaten Rokan Hilir, Provinsi Riau, Indonesia. Temuan dalam penelitian menjelaskan bahwa kebiasaan merokok di hadapan anak berpotensi merangsang tindakan merokok anak. Larangan atau himbauan untuk tidak merokok apabila tidak desertai tindakan kongkret malah menjadi impuls pemicu tingginya prilaku merokok remaja. Dalam penelitian ini dijelaskan bagaimana impuls tersebut berproses dan terbentuk dalam tindakan prilaku bagi remaja menggunakan perspektif perilaku sosiologis.Kata kunci: prilaku merokok, orang tua, remaja, impuls, kesehatan